Identification and Characterization of Known Biallelic Mutations in the IFT27 (BBS19) Gene in a Novel Family With Bardet-Biedl Syndrome - Schaefer, Elise; Delvallée, Clarisse; Mary, Laura; Stoetzel, Corinne; Geoffroy, Véronique; Marks-Delesalle, Caroline; Holder-Espinasse, Muriel; Ghoumid, Jamal; Dollfus, Hélène; Muller, Jean (Frontiers in Genetics, 2019)
Bardet-Biedl Syndrome (BBS; MIM 209900) is a rare ciliopathy characterized by retinitis pigmentosa, postaxial polydactyly, obesity, hypogonadism, cognitive impairment and kidney dysfunction. At the time of this study, 22 BBS genes have been identified to cause the disease. Here, we report a family mutated in IFT27/BBS19 presenting with typical BBS features (retinitis pigmentosa, postaxial polydactyly, obesity, cognitive impairment and atrioventricular septal defect). Using whole exome sequencing, two compound heterozygous mutations were found in the proband (NM_006860.4:c.[104A>G];[349+1G>T], p.[Tyr35Cys];[?]) consistent with the expected autosomal recessive inheritance mode. These two mutations have already been reported but independently in other families and lacking either familial segregation or functional validation. This is the third report of IFT27 mutations in BBS patients confirming IFT27 as a BBS gene (BBS19). Furthermore, this highlights the implication of the IFT-pathway in the pathomechanism of BBS with mutations in IFT27, IFT172 and IFT74.